Functional leaf trait diversity of 10 tree species in Congolese secondary tropical forest - Steppe, K. (2017)
The Congo Basin has a large secondary forest area. Nevertheless, global plant trait databases lack substantial data from this biome and functional trait diversity is largely unknown. We analysed a unique leaf trait dataset (specific leaf area, nutrient and isotope concentrations) collected from 88 individual trees belonging to 10 different species in tropical lowland forest in the Democratic Republic of the Congo. The trait data were found to be consistent with global datasets. δ 15 N was the only trait significantly influenced by plot location. For all other leaf traits, shade tolerance was a significant factor. The species factor was significant within each shade tolerance class. This shows that shade tolerance is an important but not exclusive factor determining functional diversity. Tree height had significant influence on δ 13 C, specific leaf area and area-based nutrient concentrations. Higher individual trees had thicker sun-adapted leaves, regardless of the species. A principal component analysis (PCA) resulted in three significant ordination axes: leaf-thickness, N-content and P-content. By hierarchical clustering of the PCA scores, four functional groups were distinguished. This showed that species with diverse strategies coexisted in the ecosystem.